PKM Penerapan Teknologi Aplikasi Zakat Berbasis Mobile Application Pada Masjid Raudhotul Jannah Komplek Taman Cipulir Estate - Agus Umar Hamdani; Indra Indra; Puspita Rani; Riskiana Wulan (I-Com: Indonesian Community Journal, 2024)
Optimizing the management of zakat funds can be used to empower the economy of the poor so as to reduce poverty levels. Therefore, there needs to be a body tasked with managing zakat funds so that they can provide optimal contributions to the community. The zakat administrators of the Roudhotul Jannah Taman Cipulir Estate Mosque were given the task of collecting and managing zakat funds from mosque congregations. This service is carried out by writing in a book and inputting zakat funds through the zakat management website. The weakness of the current zakat management is that the data collection process for muzakki and mustahiq is still carried out by zakat administrators, causing the administration process to be slow. Apart from that, prospective muzakki who are outside the mosque environment cannot be served well. Based on the conditions above, training and assistance in managing zakat is needed for the zakat administrators of the Raudhotul Jannah Mosque in order to create optimal services. The method used in this activity is training and mentoring. This activity takes the form of training on the use of mobile application-based zakat management applications for zakat administrators. Based on the evaluation of the implementation of this community service activity, the percentage of partner satisfaction was 88% and the percentage of mobile application-based zakat management application testing was 96%, so it is hoped that there will be an increase in knowledge and understanding regarding good zakat governance and can continue to be used in the future..